Régularisation d’une surface de contact par approximation diffuse - Chamoret, Dominique; Rassineux, Alain; Villon, Pierre; Bergheau, Jean-Michel (European Journal of Computational Mechanics, 2002)
The purpose of this paper is to propose a new technique to regularise a contact surface generated by the finite element method. The non-smoothness of these surfaces is one of the fundamental problems for the numerical treatment of contact in large slips. The method used to smooth the contact surfaces rests on the technique of diffuse approximation based on the nodes of the mesh. The new geometrical model described, the elementary contact residual vector and the stiffness matrix are expressed using the properties of the smooth surface.